The Role of Artificial Intelligence (Chat GPT) in the Development of Technology and Communication - Rohmah, Salwa Nur; Haqqu, Rizca (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research investigates the role of ChatGPT in human-machine communication, focusing on interaction attributes and user perceptions. The study employs qualitative methods, including interviews with ChatGPT users, word cloud analysis using NVivo 12 Pro, and observation of interactions. Results highlight five frequently occurring codes: "chat," "person," "ChatGPT," "task," and "communication." These findings suggest that ChatGPT is perceived both as a communicative tool and a communicative subject, with AI literacy being crucial for its effective use. The research contributes significantly to understanding the development of technology and communication, showcasing ChatGPT’s potential to transform human-machine interactions. It demonstrates how ChatGPT can improve efficiency, creativity, and our understanding of artificial intelligence. The study also explores the comparison between human-human and human-machine communication, emphasizing the unique role of ChatGPT in modern communication dynamics. This research underscores the importance of integrating AI education into curricula and providing clear guidelines for ethical and effective use of AI technologies like ChatGPT